2021
DOI: 10.1051/e3sconf/202128603013
|View full text |Cite
|
Sign up to set email alerts
|

Biological water treatment in a recirculating aquaculture system

Abstract: Biological water filtration is a process by which toxic compounds are removed from water using organisms. A well-sized biological filter is extremely important as part of a recirculating aquaculture system for fish farming. Biological water filtration equipment in aquaculture recycling systems is a technological set that restores the vital qualities of wastewater from fish ponds, thus allowing its reuse

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Poor water conditions can also inhibit fish growth performance. Aquaculture ponds that contain high particles from the left-over feed and fish excretion can increase the NH3, NO2, TDS in water, and decrease the pH and DO, which all these parameters are needed to be in the optimum level to accelerate the fish growth (de Silva et al, 2022;Laza et al, 2021;Setyono et al, 2023). Studies have shown that exposure to suspended sediments can impact the gill structure and microbiome of fish larvae, potentially influencing the distribution patterns of fish assemblages (Hess et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Poor water conditions can also inhibit fish growth performance. Aquaculture ponds that contain high particles from the left-over feed and fish excretion can increase the NH3, NO2, TDS in water, and decrease the pH and DO, which all these parameters are needed to be in the optimum level to accelerate the fish growth (de Silva et al, 2022;Laza et al, 2021;Setyono et al, 2023). Studies have shown that exposure to suspended sediments can impact the gill structure and microbiome of fish larvae, potentially influencing the distribution patterns of fish assemblages (Hess et al, 2015).…”
Section: Introductionmentioning
confidence: 99%